An Analytical Method for Determining the Load Distribution of Single-Column Multibolt Connection - Nirut Konkong; Kitjapat Phuvoravan (Advances in Civil Engineering)
The purpose of this research was to investigate the effect of geometric variables on the bolt load distributions of a cold-formed steel bolt connection. The study was conducted using an experimental test, finite element analysis, and an analytical method. The experimental study was performed using single-lap shear testing of a concentrically loaded bolt connection fabricated from G550 cold-formed steel. Finite element analysis with shell elements was used to model the cold-formed steel plate while solid elements were used to model the bolt fastener for the purpose of studying the structural behavior of the bolt connections. Material nonlinearities, contact problems, and a geometric nonlinearity procedure were used to predict the failure behavior of the bolt connections. The analytical method was generated using the spring model. The bolt-plate interaction stiffness was newly proposed which was verified by the experiment and finite element model. It was applied to examine the effect of geometric variables on the single-column multibolt connection. The effects were studied of varying bolt diameter, plate thickness, and the plate thickness ratio (t2/t1) on the bolt load distribution. The results of the parametric study showed that the t2/t1 ratio controlled the efficiency of the bolt load distribution more than the other parameters studied.